Content Marketing Strategy on the TikTok Application: Investigating Consumer Drivers of Impulsive Buying Behavior in Purchasing Tanasol Products - Ni Nyoman Sri Anjani; Nyoman Sri Manik Parasari (Economics and Digital Business Review, 2026)
This study aims to analyze the TikTok content marketing strategy used by Tanasol, a local women's sandal brand from Bali, and to identify factors driving consumer impulsive buying behavior. The study employs a qualitative descriptive approach using a case study method. Data were collected through in-depth interviews with three cross-generational consumers, the business owner, and Tanasol's marketing team, supplemented by non-participatory observation of TikTok content and digital documentation. Data analysis followed the Miles and Huberman interactive model. Results indicate that content strategies based on visual realism, simple storytelling, thematic promotions, and TikTok Shop integration effectively drive impulsive purchases. Key drivers of impulsive buying include honest and realistic product visuals, ease of TikTok Shop features, affordable pricing, high trust levels, and situational-emotional factors. These findings are analyzed through Ajzen's (1991) Theory of Planned Behavior framework, demonstrating synergy between positive consumer attitudes, subjective norms from social proof, and high perceived behavioral control. This study affirms that local SME brands can compete effectively in TikTok's digital ecosystem through organic approaches based on emotional proximity and content authenticity, without relying on major influencers.